Interaction of moisture content and fat content on puffing properties of expanded-product from native rice starch - Jiamjariyatam, Rossaporn; Atiwittaporn, Suriya (Food and Applied Bioscience Journal, 2017)
Starch-based snacks and ready-to-eat breakfast cereal are commonly made in the form of puffed products. Puffed products are appreciated mainly for their lightness and crispness. One of the factors responsible for the qualities of puffed products is moisture and shortening content. This research aims to investigate the effects of moisture content and shortening content on pellet microstructure and puffing qualities. The rice starch mixture with amylose content (AC) of 5.05% was prepared by mixing native waxy and non-waxy rice starches. Starch pastes were cooked and aged at 4°C for 24 h. The aged slabs were dried. Deep-frying was then used for puffing. The pellet with 15% moisture content provided the maximum expansion. There was the interaction between moisture content and fat content on the expansion ratio and overall characteristic of puffed product. From Scanning Electron Microscope, starch pellet had cavities separated by very thin wall. Cavity size of expanded puffed product decreased as moisture and fat increased. From sensory evaluation of puffed product, increasing moisture and fat and their interaction caused in an acceptance of product crispness and puffiness.